Pleasure and Poetics as Tools for Transformation in Aśvaghoṣa’s mahākāvya - Julie Regan (Religions, 2022)
Why does Aśvaghoṣa (c. second century C.E.), the first known author of a Buddhist literary work, choose a literary genre (mahākāvya) with erotic scenes and elaborate poetic language to present the truth that leads to liberation? This question, which has puzzled and fascinated scholars since the first known translations of Buddhacarita and Saundarananda, is often answered by turning to a statement Aśvaghoṣa makes, which suggests that such methods are necessary to reach his worldly audience, who are interested only in pleasure and not liberation. Dismissed as mere sugarcoating for “the bitter truth” of the Buddhist doctrine, the impact of the pleasures and poetics of Aśvaghoṣa’s work upon the reader has rarely been explored. Methods emphasizing a hermeneutic approach to scholarship, focused on interpreting what such works have to say, has meant less attention to what these works do to transform readers (their poetics). However, new attention to the literary aspects of Aśvaghoṣa’s mahākāvya, a genre of long-form narrative literature known for its poetic features, as well as recent scholarship on the Sanskrit courtly culture for which it was produced, suggest pleasure is a central feature. In this article I argue that comparative analysis of the dramatic structure of Buddhacarita and Saundarananda demonstrates that Aśvaghoṣa uses his ability as a dramatist to employ rasa, pleasurable aesthetic experiences, staged to gradually transform the minds of readers. I argue that as the plots of Buddhacarita and Saundarananda unfold, and the Buddha and his brother Nanda go from erotic and ascetic scenes to the sites of liberation, readers are engaged and moved in ways that refine their perceptions, introducing forms of concentration and insight not unlike the Buddhist practices depicted in these works.